The Effect of Evaluation Model on Accountability of School Counselor - Badrujaman, Aip; Suherman, Suherman; Wahyuni, Eka (Universitas Ahmad Dahlan, 2018)
The purpose of the current study was to find out the effect of the evaluation model on the school counselor's accountability in State Junior High School of East Jakarta in carrying out guidance curriculum. The study employed waiting-list control group true experimental research. The subject of the study was thirty-three school counselors of State Junior High Schools of East Jakarta who were randomly selected and assigned into experimental and control group. The instrument utilized in the study was accountability scale consisting of 3 subscales including Accountability scale in the version of Headmaster, Homeroom teacher, and students. The school counselor's accountability score which was a composite score of three subscales was analyzed using ANAKOVA in order to find out the effect by controlling the variable of attitude toward guidance curriculum evaluation and guidance curriculum evaluation skill. The result of the study showed that accountability-oriented guidance curriculum evaluation model could not improve the whole accountability components of school counselors of state junior high schools of East Jakarta in carrying out guidance curriculum. There was only one accountability component that was affected by the evaluation model namely the component of explaining guidance curriculum to the stakeholder. The result of the study provides contribution to the Educational Service (Dinas Pendidikan) and the school counselors as consideration in carrying out training activity in order to improve guidance curriculum evaluation skill.